Eosinophilic oesophagitis: investigations and management. Issue 1063 (24th March 2014) - Kumar, Mayur; Sweis, Rami; Wong, Terry
Abstract: Eosinophilic oesophagitis (EO) is an immune/antigen mediated, chronic, relapsing disease characterised by dysphagia, food bolus impaction and a dense oesophageal eosinophilic infiltrate. Characteristic endoscopic features include corrugated rings, linear furrows and white exudates, but none are diagnostic. Despite its increasing prevalence, EO remains underdiagnosed. There is a strong association with other atopic conditions. Symptoms, histology and endoscopic findings can overlap with gastro-oesophageal reflux disease. Currently endoscopy and oesophageal biopsies are the investigation of choice. Oesophageal physiology studies, endoscopic ultrasound, impedance planimetry and serology may have a role in the diagnosis and monitoring of response to therapy. Acid reducing medication is advocated as first line or adjuvant therapy. Dietary therapy is comprised of elimination diets or can be guided by allergen assessment. In adults, topical corticosteroids are the mainstay of therapy. Endoscopic dilatation is safe and effective for the treatment of non-responsive strictures. Other therapeutic options (immunomodulators, biological agents, leukotriene receptor antagonists) are under investigation.